DEVELOPING DIGITAL TEACHING MODULE OF SOCIAL-SCIENCE SUBJECT BASED STEAM METHOD FOR GRADE FOUR ELEMENTARY SCHOOL STUDENTS: Pendidikan Dasar - Ni Nyoman Rusmini; I Wayan Lasmawan; I Made Candiasa (Indonesian Journal of Educational Development (IJED), 2023)
Digital learning modules continue the trend for future literacy modules. The covid 19 pandemic, which has paralyzed practically all sectors of economic and educationally life, has played a role in accelerating to use of digital learning modules. Student are forced to study individually from home using digital platforms. A digital modules is a digital book expected to enable students to study independently, with or without a facilitator. This research aims to develop a digital learning module on STEAM based method science-social subjects for graders. This research used the EDDIE development model, which consists of five phases; analyze, design, implementation and evaluate. The characteristic of digital learning modules include five parts; components, displys, materials, learning activities and research systems. Content validation used the Gregory formula with the results of the validity test classifiled as valid; material and media feasibility test used LORI formula with test results included in the very feasible category; practically testing used the User Experience Questions (UEQ) quistionaire method with test results included in the excellent or very hight category; and the effectiveness of the product was tested using an assessment in the form of essay with everage student score of 82.4, which is incluede in the 90% completeness category. The development of digital teaching modules aims to improve students’ ability to understands STEAM based method on social-science subjects, increase student achievement in practicing module materials in the form of literacy and numeracy through worksheet and projects activities, and improve students’s ability in digital technology teaching module independently, which are easy to use anytime-anywhere.